Human colonic intraepithelial lymphocytes regulate the cytokines produced by lamina propria mononuclear cells - P. Hoang; J. P. Dehennin; Li Li; C. Sibille; A. Geubel; J. P. Vaerman (Mediators of Inflammation)
Using an in vitro autologous human system, the immunomodulatory function of colonic intraepithelial lymphocytes (IEL) on cytokine production by lamina propria mononuclear cells (LPMNC) has been investigated. In contrast to LPMNC, colonic IEL produced only low amounts of IL-10, interferon-γ and interleukin-2. However, co-culture experiments (IEL + LPMNC) have shown that IEL can enhance the PHA-induced synthesis of IL-2 and interferon-γ, but not IL-10 by LPMNC. Using a transwell filter culture system apparatus, this effect was shown not to require a cell-to-cell interaction. Thus, IEL in vitro may modulate the cytokine synthesis of LPMNC, through the production of soluble factors. This may prove highly relevant in the in vivo immune activation of the gastrointestinal mucosa.